Trash to Cash: The Effort to Turn Sticks from Palm Tree Waste into Creative Products in Pondok Pabrik Village - Nanda Safarida; Juli Dwina Puspita Sari; Rifyal Dahlawy Chalil (PT FORMOSA CENDEKIA GLOBAL, 2023)
In order to enhance skills that may be utilized to support the family economy, community service projects are being implemented through training in the production of decorative brooms and food containers out of sticks obtained from palm tree waste. The method's stages include observation, discussion, demonstration, and hands-on practice, which are carried out by planning, carrying out, and evaluating. The results of this activity are expected to improve the participants' knowledge, comprehension, and creativity, therefore creating business opportunities as well as achieving economic independence.